Clinical and economic burden of achondroplasia in the United States: results from a retrospective, observational study - Nadia Merchant; Jose Alvir; Paulette Negron Ericksen; Jane Loftus; Jose Francisco Cara; Alison Slade; Michael P. Wajnrajch; Christine L. Baker (Orphanet Journal of Rare Diseases)
Abstract Background Achondroplasia, a disease characterized by disproportionate short stature and increased morbidity, affects daily function and quality of life over the lifetime of the individual. However, data are limited on its economic impact, especially related to healthcare resource utilization (HCRU) and associated costs. This study aimed to characterize the clinical and economic impact of achondroplasia in the US relative to matched non-achondroplasia controls stratified by pediatric and adult populations. Methods This retrospective study used data from the IQVIA PharMetrics Plus national claims database from January 2008 to December 2021. Individuals diagnosed with achondroplasia (index event) between July 2008 and December 2020 were matched on age and sex (1:2 ratio) to non-achondroplasia controls. General comorbidities were evaluated in the pediatric and adult populations. All-cause HCRU and direct medical costs were determined for the 12-month post-index period; out-of-pocket (OOP) costs were also determined. Study variables were analyzed using descriptive statistics. Results A total of 530 individuals with achondroplasia (47.7% pediatric and 52.3% adults) were matched with 1,060 controls. Individuals in the achondroplasia cohort had higher overall comorbidity burdens than controls. HCRU was higher in the achondroplasia cohort relative to controls, with outpatient visits the most frequently used resource. Inpatient visits were the primary driver of mean (SD) total costs, which were 14-fold higher than controls ($28,386 [$259,858] vs $2,031 [$5,418]) in pediatric individuals, and 4-fold higher in adults $21,579 [$58,817] vs $4,951 [$13,020]); prescriptions accounted for 4.7% and 7.4% of total costs in the pediatric and adult achondroplasia cohorts, respectively. The OOP costs were approximately 3-fold higher in both pediatric and adult individuals with achondroplasia relative to controls. Conclusions Individuals with achondroplasia are characterized by a higher comorbidity burden and substantially higher HCRU and related costs relative to matched controls. The results also suggest that despite high HCRU and costs, individuals with achondroplasia likely are not seen by providers early enough nor are they necessarily seen by appropriate specialists, indicating a need for improved care and disease management.